The Trend of Emerging Identity Politics in Indonesia and the Challenge in Fostering Social Cohesion: Lesson Learned from Jakarta Provincial Election - Kamilia Hamidah (Institut Agama Islam Negeri Madura, 2018)
Social cohesion is one important social capital to support the ongoing process of development programs and also as a guarantee for social stability. The good indication of social cohesion in a society characterized by a strong sense of belonging that encourages the desire to work together. This paper will substantively elaborate how Jakarta provincial election has strengthen the identity politics which posed great challenge to the constructed social cohesion. This paper will try to answer why identity politics was used as strategic political campaign strategies to generate massive support and how the confusion to the sentiment of identity politics has turned into the emergence of social gap in the society which leads to the disturbance of existing pattern of social cohesion. The explanation from this paper build on the basis of different media analysis throughout Jakarta provicial election on the issue related SARA (religion, ethnic and group). From this study, shows that the issue related SARA in Jakarta provincial election case was the culmination of the political ideology confrontation which give subsequent impact to the equilibrium of social cohesion in the society.